1996
DOI: 10.1172/jci118789
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of the anti-Fas antibody on arthritis in HTLV-1 tax transgenic mice.

Abstract: We have recently demonstrated Fas-mediated apoptosis in the synovium of patients with rheumatoid arthritis (RA) and suggested that it may be one factor responsible for the regression of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 30 publications
7
60
1
2
Order By: Relevance
“…Based on these findings, we postulated that active induction of apoptosis in proliferative rheumatoid synovium may be useful as a new mode of therapy for RA. 14 In support of our hypothesis, we have recently demonstrated that intra-articular administration of anti-Fas mAb in the human T cell leukemia virus type 1 (HTLV-1) carrying mice, which was established by our group as a suitable model of human RA, improved the paw swelling and histologic features of arthritis by inducing apoptosis of synoviocytes and mononuclear cells in the inflamed synovium. 14 In contrast, administration of antiFas mAb or soluble FasL in mice was cytotoxic to other Fas-bearing tissues such as the liver, and induced fulminant hepatitis.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Based on these findings, we postulated that active induction of apoptosis in proliferative rheumatoid synovium may be useful as a new mode of therapy for RA. 14 In support of our hypothesis, we have recently demonstrated that intra-articular administration of anti-Fas mAb in the human T cell leukemia virus type 1 (HTLV-1) carrying mice, which was established by our group as a suitable model of human RA, improved the paw swelling and histologic features of arthritis by inducing apoptosis of synoviocytes and mononuclear cells in the inflamed synovium. 14 In contrast, administration of antiFas mAb or soluble FasL in mice was cytotoxic to other Fas-bearing tissues such as the liver, and induced fulminant hepatitis.…”
Section: Discussionsupporting
confidence: 57%
“…14 In support of our hypothesis, we have recently demonstrated that intra-articular administration of anti-Fas mAb in the human T cell leukemia virus type 1 (HTLV-1) carrying mice, which was established by our group as a suitable model of human RA, improved the paw swelling and histologic features of arthritis by inducing apoptosis of synoviocytes and mononuclear cells in the inflamed synovium. 14 In contrast, administration of antiFas mAb or soluble FasL in mice was cytotoxic to other Fas-bearing tissues such as the liver, and induced fulminant hepatitis. 15,16 While the above results provide strong support for a potential therapeutic use of RA synoviocyte apoptosis-inducing agents, they also indicate that further …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, growth of an intraperitoneal lymphoma can be controlled by intraperitoneal CD95 ligand applied locally (Rensing-Ehl et al, 1995), and intra-articular application of CD95 antibodies can control arthritis (Fujisawa et al, 1996), both in the absence of systemic toxicity. Further, circulation of CD95 ligand is not inevitably lethal (Sato et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A high amount of tax mRNA was amplified in synovial cclls from these HTLV-I tax-transgenic mice, and sensitivity to anti-Fas antibody was acquired in vivo (27). Moreover, Yoshiki and colleagues recently established the HTLV-I env-pX-transgenic rat and demonstrated not only dcstructive arthropathy, but also SS, vasculitis syndrome, and polymyositis with immune dysregulation in these animals (Yoshiki T: personal communication).…”
Section: Pathogenesis Of Htlv-i Arthropathymentioning
confidence: 99%